Chemical stability and electrical properties of Ba1−xCaxCe0.8Gd0.2O3−δ (0 ≤ x ≤ 0.06) proton conductor. (15th February 2023) - Luo, Yadan; Li, Ying; Huang, Wenlong; Dayaghi, Amir Masoud; Zhou, Gaopeng; Ding, Yushi; Zhang, Ning; Ni, Peiyuan
Abstract: The effect of Ca content on chemical stability and electrical properties of Ba1− x Ca x Ce0.8 Gd0.2 O3−δ (BCCG, 0 ≤ x ≤ 0.06) proton conducting electrolyte is investigated in this work. The BCCG pellets were fabricated via a solid-state reaction method and high-temperature sintering at 1600 °C for 10 h in air. In XRD patterns, BCCG exhibited an orthorhombic phase, and the diffraction peaks of calcium-modified BaCe0.8 Gd0.2 O3−δ (BCG)-based samples shifted toward the high-angle side compared to BCG, indicating that Ca 2+ occupies the A site. The chemical stability showed that adding a small amount of Ca 2+ improves the stability against water while it deteriorates the stability in CO2 -containing atmosphere. The highest conductivity was obtained for 1% Ca substitution ( x = 0.01, BCCG1), where it increased from 1.1 × 10 −3 to 2.8 × 10 −3 S cm −1 at 400 °C and from 1.7 × 10 −2 to 3.1 × 10 −2 S cm −1 at 800 °C compared to that of x = 0. The partial conductivities were greater for BCCG1 compared with BCG material. Proton conductivity was dominant for BCCG1 sample at 600 °C. Graphical abstract: Image 1 Highlights: The introduced Ca 2+ ions were located in the same positions as the original Ba 2+ ions in BaCe0.8 Gd0.2 O3−δ (BCG). Ba0.99 Ca0.01 Ce0.8 Gd0.2 O3−δ showed the highest conductivity in all samples. Transference numbers of BaCe0.8 Gd0.2 O3−δ and Ba0.99 Ca0.01 Ce0.8 Gd0.2 O3−δ were compared.